2011
DOI: 10.1016/j.adolescence.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Identity in university students: The role of parental and romantic attachment

Abstract: In this study with 236 Portuguese university students, we examined two competing models for understanding identity. In the first model, the direct independent effects of parental and romantic attachment on identity were tested. The second model examined the mediating role of romantic attachment representations in the link between parental attachment and identity. The participants completed measures of parental and romantic attachment at the beginning of the freshman year (Wave 1), and a measure of identity dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…Looking across these theories, some scholars argue that identity and intimacy development co‐occur during adolescence (Montgomery, 2005; Pittman et al., 2011). Indeed, research shows that an adolescent's feelings of closeness, support, or security within close relationships, whether family, peer or romantic, are associated with efforts to form an identity (Avila, Cabral, & Matos, 2012; Kerpelman et al., 2012; Pittman, Kerpelman, Soto, & Adler‐Baeder, 2012). Other studies show an association between psychosocial intimacy and identity constructs (e.g., Archer & Grey, 2009; Montgomery, 2005).…”
Section: Identity and Intimacy In Adolescencementioning
confidence: 99%
“…Looking across these theories, some scholars argue that identity and intimacy development co‐occur during adolescence (Montgomery, 2005; Pittman et al., 2011). Indeed, research shows that an adolescent's feelings of closeness, support, or security within close relationships, whether family, peer or romantic, are associated with efforts to form an identity (Avila, Cabral, & Matos, 2012; Kerpelman et al., 2012; Pittman, Kerpelman, Soto, & Adler‐Baeder, 2012). Other studies show an association between psychosocial intimacy and identity constructs (e.g., Archer & Grey, 2009; Montgomery, 2005).…”
Section: Identity and Intimacy In Adolescencementioning
confidence: 99%
“…Responses are provided on a 6-point Likert scale ranging from 1 ( totally disagree ) to 6 ( totally agree ). Several studies have established that the RAQ has strong psychometric properties (e.g., Ávila, Cabral, & Matos, 2012; Oliveira, & Costa, 2009). Ávila et al (2012) found strong and expected links between the RAQ and the widely used Experiences in Close Relationships Scale (ECR; Brennan, Clark, & Shaver, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…El sentimiento de aceptación institucional del sistema educativo (Black et al, 2009;Vorwek, 2009) constituye la lógica explicativa de estas percepciones por diversas razones: primero, la población de estudiantes que accede a la educación superior ha interiorizado la necesidad de continuidad en etapas progresivas en el sistema (Ávila, Cabral,& Matos, 2012). También, el flujo institucional del sistema educativo conserva rutinas y regulaciones, aceptadas por estudiantes, en referencia a la enseñanza, dependencia respecto al conocimiento del docente, valoración de la reproducción de contenidos y valoración de la calificación como indicativo de éxito escolar (Ounjit, 2012).…”
Section: Conclusiones E Implicaciones Para Futuros Estudiosunclassified